RESPON MASYARAKAT KELURAHAN LUBUK PUDING DALAM MENONTON SIARAN TV-3 MALAYSIA DI KECAMATAN PULAU BURU KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Helmasari Helma (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
Culture between SIJORI (Singapore-Johor-Riau) has many similarities First Johor Malaysia is almost similar to Malay culture such as Malay Joget, Zapin Melayu, Tanjung Balai Karimun Gazal, Secondly the creation of a constructive Malay cultural pattern imbalances Indonesian culture. Furthermore, the three descendants of Tanjung Balai Karimun in the 1940 era migrated to Malaysia, the Fourth Malay Malay Family originated from Tanjung Balai Karimun, Fifth in terms of Karimun language similar to the Malaysian language at the same time as Malaysia, the Sixth Family (Relationship) visited routine 35 minutes a day to Malaysia using Malaysia Ferry to Malaysia (Johor Bharu) specifically Kukup commuting every one (1) once. So that it is not so difficult for Malaysian television broadcasts to be received and accepted by the majority of the people of Riau Islands, especially in Lubuk Puding Village, Buru Island District, Karimun Regency, which historically has a closeness to the soul of the